Postępowanie dowodowe przed Europejskim Trybunałem Praw Człowieka zagadnienia ogólne - Trybka, Wiktor (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Evidentiary proceedings before the European Court of Human Rights are the most important step in the whole procedure. Guidelines for the establishment of facts have been set out in the European Convention for the Protection of Human Rights and Fundamental Freedoms and clarified in the Rules of the European Court of Human Rights. The purpose of this paper is to present the outline of the procedure with the indication of the place of evidence investigation and the presentation of its progress. In the description of the evidence investigation the problem of the burden of proof and its evaluation was emphasized. In order to carry out a comprehensive description of this stage of the procedure, the author referred to the proceedings before the Court of Justice of the European Union and the solutions adopted in Polish criminal and civil law. Evidence such as witneses’ statements and opinions by experts was also presented. It has been compared with the measures used to establish facts in the course of proceedings before the Court of Justice of the European Union. From the point of view of the increasing number of complaints to Strasbourg the subject of this article seems to be particularly important.
Keywords: Europejski Trybunał Praw Człowieka; postępowanie dowodowe; ogólne problemy